2019
DOI: 10.3892/etm.2019.8267
|View full text |Cite
|
Sign up to set email alerts
|

Effects of simvastatin‑loaded PLGA microspheres on treatment of rats with intervertebral disk degeneration and on 6‑K‑PGF1α and HIF‑1α

Abstract: Effects of simvastatin-loaded PLGA sustained release microspheres on the treatment of rats with intervertebral disk degeneration (IVDD) and on 6-keto-prostaglandin F1α (6-K-PGF1α) and hypoxia inducible factor-1α (HIF-1α) were investigated. Eighty female rats were selected and randomized into a model group (modeled for IVDD), a treatment group (modeled and treated with simvastatin-loaded PLGA sustained release microspheres), a sham operation group (only operated without excision), and a control group (not treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…For example, Yan et al prepared a hydrogel containing the hydrophobic simvastatin using the thermosensitive substance poly­( dl -lactide- co -glycolide)-poly­(ethylene glycol)-poly­( dl -lactide- co -glycolide) (PLGA-PEG-PLGA) to treat bone deformities in rats. Besides, Zhu et al developed PLGA microspheres containing simvastatin for the treatment of IVDD. The microspheres had a drug loading of 22.85 ± 1.85% and could be sustained for 200 h with a cumulative release rate of over 80%.…”
Section: Therapeutic Agent Therapy For Ivddmentioning
confidence: 99%
“…For example, Yan et al prepared a hydrogel containing the hydrophobic simvastatin using the thermosensitive substance poly­( dl -lactide- co -glycolide)-poly­(ethylene glycol)-poly­( dl -lactide- co -glycolide) (PLGA-PEG-PLGA) to treat bone deformities in rats. Besides, Zhu et al developed PLGA microspheres containing simvastatin for the treatment of IVDD. The microspheres had a drug loading of 22.85 ± 1.85% and could be sustained for 200 h with a cumulative release rate of over 80%.…”
Section: Therapeutic Agent Therapy For Ivddmentioning
confidence: 99%
“…As tissue engineering and regenerative medicine techniques continue to develop, microsphere-based regenerative therapies are gradually being used for IVDD, which has the opportunity to change the current dismal situation. In recent studies, microsphere systems carrying bioactive substances ( Sawamura et al, 2009 ; Yuan et al, 2013 ; Yan et al, 2014 ; Xu H. et al, 2020 ; Xu Y. et al, 2020 ; Bian et al, 2021 ; Shen et al, 2022 ), drugs ( Liang et al, 2013 ; Murab et al, 2015 ; Tellegen et al, 2018 ; Rudnik-Jansen et al, 2019 ; Zhu et al, 2020 ; Wiersema et al, 2021 ), cells ( Liang et al, 2013 ; Li et al, 2014 ; Xia et al, 2019 ), and gene regulators ( Feng et al, 2017 ; Feng et al, 2020 ; Chang et al, 2022 ) have been injected into IVD tissues in a minimally invasive manner to exert corresponding therapeutic effects locally ( Figure 5 ). It is worth mentioning that therapeutic substances (except cells) are slowly released locally by self-diffusion, microsphere degradation, or dissolution.…”
Section: Application Of Microsphere-based Delivery Systems In Ivddmentioning
confidence: 99%
“…For example, the application of simvastatin within a degenerative IVD may slow the degenerative process to some extent ( Than et al, 2014 ). One study reported the effect of simvastatin-loaded PLGA microspheres in a rat model of IVDD ( Zhu et al, 2020 ). Simvastatin microspheres showed a better release profile, with a cumulative release of more than 80%.…”
Section: Application Of Microsphere-based Delivery Systems In Ivddmentioning
confidence: 99%
“…Biodegradable microparticles based on PLGA polymers have proven to be useful drug delivery systems in biomedical applications such as adjuvant/vehicle for vaccines, tissue engineering, sustained-release systems or cancer treatment 113 , 114 , 115 , 116 , 117 . In 2012, the FDA approved Bydureon® for the treatment of DM 36 .…”
Section: Formulation Strategies To Improve the Pharmacokinetics And B...mentioning
confidence: 99%